Analisis Pertumbuhan Ekonomi dan Ketimpangan Distribusi Pendapatan Provinsi Bali - Kurniawan, Rendi; Huda, Syamsul (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
This study aims to determine the Regency / City Classification in Bali Province based on the Klassen Typology, the condition of income distribution inequality between districts / cities, the relationship between income distribution inequality with per capita income, and whether the relationship forms the U-Reverse Kuznets Curve. This research is an analysis of secondary data obtained from BPS Bali Province. The analytical model used is Klassen Typology analysis, Williamson Index, Product Moment Correlation (Pearson). Klassen's Typology Results, Badung Regency and Denpasar City are included in Quadrant I area, Gianyar Regency is included in Quadrant III area, and the remaining 6 Regencies are included in Quadrant IV area. Furthermore, the Williamson Index Calculation in the Year of Observation shows that there is an imbalance in the Province of Bali which shows a downward trend. While the calculation result of Product Moment Correlation (Pearson) shows a very strong relationship between the Williamson Index and the Per capita GRDP and is negative, but the relationship does not form the Kuznets Curve to be a U-Reverse letter.